Особливості побудови системи аналітичного обліку розрахунків за виплатами працівникам - Kuz, Vasyl (Причорноморський науково-дослідний інститут економіки та інновацій, 2020)
У статті розглянуто підходи до організації аналітичного обліку розрахунків за виплатами працівникам. Ідентифіковано сукупність видів виплат та масив супутніх даних, що визначаються нормативно-правовим забезпеченням облікового відображення розрахунків за виплатами працівникам. Запропоновано до застосування модель організації аналітичного обліку розрахунків за виплатами працівникам, яка передбачає ідентифікацію релевантних аналітичних розрізів (за типами трудових відносин; за функціями, що виконуються працівниками; у розрізі працівників; за видами виплат відносно фондів оплати праці; за видами виплат), що забезпечують формування, у межах облікового процесу, показників фінансової, статистичної, податкової та спеціальної звітності, а також дозволяють посилити виконання обліковою системою контрольних та аналітичних функцій при обчисленні виплат за невідпрацьований час, нарахувань на виплати працівникам, утримань із них та інформаційних функцій при управлінні персоналом тощо. The article considers the approaches to the organization of analytical accounting of payments to employees. It ie established that the performance of accounting, calculation-analytical and informational tasks bх the subject of accounting requires a large-scale division of payments to employees into types according to different criteria and features, which complicates the construction of an effective system of analytical accounting of payments to employees. The eet of types of payments and the array of related data which ie determined bх the regulatory and legal support of the accounting reflection of payments to employees are identified. It ie established that the legislative regulation provides identification of payments that differ in content of occurrence and purpose, payments for which there are potentially different rules of recognition and evaluation, priority (basic) payments, which are then used for calculation other staff payouts, payments that characterize the directions of disclosure information in order to inform external users, determination tax liabilities and state social insurance obligation, conducting state statistical observations, etc. A model of organization of analytical accounting of payments to employees is proposed, which provides for the identification of relevant analytical sections (by types of labour relations; by functions which are performed by employees; by employees; by types of payments in relation to wage funds; by types involved in the calculation of tax and other liabilities; by types of payments), that provide formation, within the accounting process, indicators of financial, statistical, tax and special statements and also allow strengthening performance by the accounting system control and analytical functions in calculation of payments for overtime, accruals for payments to employees, deductions from them and information functions in staff management, etc. Application of the proposed system of analytical accounts, in terms of using specialized software for accounting, doesn't increase the complexity of accounting operations.
Peculiarities of Construction of the System of Analytical Accounting of Calculations for Payments to Employees
Keywords: аналітичні рахунки; виплати працівникам; звітність; розрахунки за виплатами працівникам; фонд оплати праці; analytical accounts; payments to employees; statements; calculations for employee benefits; wage fund